Evaluation of oral health status for a group of orthodontic patients - Nihad Muhamed Al-Mujamaii, Karrar; Ali Ahmed Hentati, Hajer; Hafidh Taha, Zainab; Salim Altaee, Abdulhameed (Diyala Journal of Medicine, 2023)
Background: Malocclusion and fixed orthodontic appliance convoluted the ordinary oral hygiene measures, which may lead to accumulation and prolonged retention of dental plaque on tooth surfaces particularly around the orthodontic brackets and auxiliaries of the fixed orthodontic appliance. Objective: To evaluate the oral health status among a group of orthodontic patients by evaluating the plaque, gingival, calculus, and Enamel Decalcification indices. Patients and Methods: This study was conducted among 128 persons (64 with fixed orthodontic appliance as a study group and 64 without fixed orthodontic appliance as a control group. An assessment of related clinical parameters as plaque, gingival, as well as enamel decalcification indices were done. Results: The present study revealed that the mean plaque, gingival, as well as enamel decalcification indices for the total sample were (1.182±0.356), (1.230±0.269), and (1.329±0.413) respectively. Additionally, all of these indices were higher among study group (fixed orthodontic patient) than among control group (persons without orthodontic appliance) with statistically significant difference among groups for each. Conclusion: Fixed orthodontic appliance is an effective plaque retentive factor that accumulate dental plaque which is the main causative factor for development of enamel white spot lesion and periodontal disease.